Experience of naturally occurring peer support among people using psychiatric day-care in China: an interpretative phenomenology approach - Fan, Yijun; Liu, Xiao; Li, Conghong (Frontiers in Psychiatry, 2024)
Introduction: China presently does not have an established peer support system, and the efforts of peer support workers are not acknowledged in the context of the growing global trend of communitybased mental rehabilitation. This study aims to examine the first-hand experiences of persons who participate in psychiatric day-care facilities in Shanghai, China, and receive support from their peers. The goal is to gain a better understanding of how these informal peer support programs function and provide valuable knowledge for the establishment of more structured peer support programs that align with Chinese social culture.Methods: A total of 14 participants attending psychiatric day-care centres were selected for face-toface semi-structured in-depth interviews using snowball sampling. The interviews took place between July 2021 and February 2022. The text data of the interview were acquired through transcription and then augmented using the interview scripts and additional resources. The data were analysed using interpretive phenomenological analysis until the themes reached saturation.Results: A total of three overarching themes and eight corresponding sub-themes were produced: 1. reconstructing a social network: an ordinary interpersonal connection, becoming and conducting oneself, proceeding the process of adaptation in the company of peers; 2. balance and multiple roles within the relationship: selective self-exposure, managing proximity and distance; 3. sense of meaning and sense of community: supporting others while empowering oneself, love as expanding consciousness, advocating for the notion of group identity.Discussion: This study is the initial examination of the contact and naturally occurring peer support that takes place among individuals in psychiatric day-care centres in China. The study's findings revealed that participants interact with others who have undergone similar conditions in the day-care setting, enabling them to rebuild an important social network. It is crucial to consider the possible benefits of peer support, assess the obstacles, and facilitate the personal recovery of individuals with mental disorders using the theory of recovery.